PODCAST DENGAN PEMIMPIN INDONESIA IDEAL : SUATU ANALISIS KRITIS TERHADAP PERAN PODCAST SEBAGAI SALURAN KEBEBASAN MENYATAKAN PENDAPAT - Jiehan Putri Umairah (Communication and Islamic Broadcasting Studies IAIN Parepare, 2025)
This article critically analyzes the role of podcasts as a channel for freedom of expression in shaping the discourse of the ideal Indonesian leader thru Critical Discourse Analysis (CDA) based on Fairclough's model. By examining concrete cases such as KPU RI Episode 9: Ideal Leaders in the Eyes of Students (a platform for young formal and intellectual stakeholders), Podcast: Jokowi's Rants and Rocky Gerung's Ideal State Leader Version (comparing official narratives vs. sharp criticism), Episode 31: Putu Yoga: KMHDI Chairman - Ideal Political Party? (non-governmental organization perspective), as well as Applying Leadership Science from Mr. Jonan. Leaders Must Be Visible. The Leader Must Be Seen (visible leadership implementation): Research reveals how narrative framing, satirical humor, ideological rhetoric, and contrasting comparisons are used to construct an ideal leadership image while simultaneously challenging power. The findings indicate that podcasts expand the deliberative space thru long-form dialog and social media integration, enabling social criticism as a control mechanism. For example, discussions by the General Election Commission of the Republic of Indonesia (KPU RI) sparked public debate about election integrity, while Rocky Gerung's criticism of Jokowi's